2019
DOI: 10.3390/diagnostics9030084
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Remission in De Novo Breast Myeloid Sarcoma Treated with Decitabine and Radiotherapy

Abstract: Myeloid sarcoma (MS) represents a rare disease with an adverse clinical outcome for patients not candidate to acute myeloid leukemia (AML)-like chemotherapies. Here we present the case of an elderly patient affected by a bilateral breast localization of MS treated with the hypomethylating agent decitabine associated to radiotherapy. The association of the two treatment modalities has allowed an optimal and long-lasting disease control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Minoia et al. described the case of a 71-year-old woman with MS involving both breasts treated effectively with decitabine and radiotherapy with a dose of 30 Gy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Minoia et al. described the case of a 71-year-old woman with MS involving both breasts treated effectively with decitabine and radiotherapy with a dose of 30 Gy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMAs significantly enhance the immunogenicity of leukemic cells; conversely, they regulate the function of immune cell subsets such as NK cells and CD8 + T cells to enhance the killing effect. Several reports have shown that HMAs, through these mechanisms, can be used alone in elderly patients with myeloid sarcoma 30 or combination with chemotherapy 31 , radiotherapy 32 , and targeted therapy 33 to increase the antitumor effect. In patients with the TET2 mutation, decitabine may be a useful treatment option 21 .…”
Section: Discussionmentioning
confidence: 99%
“…As far as we searched English literature, eleven cases with myeloid sarcoma, including the present case, aged between 57 and 93 years, have been retrospectively reported to achieve remission with hypomethylating agents (Table 1) (Singh et al 2012;Serrao et al 2013;Modi et al 2015;Gornicec et al 2017;Katagiri et al 2017;Castelli et al 2018;Evers et al 2018;Minoia et al 2019). Decitabine and azacitidine were used for 8 and 3 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%